2018
DOI: 10.1021/acs.bioconjchem.8b00121
|View full text |Cite
|
Sign up to set email alerts
|

Selective Binding of Folic Acid and Derivatives by Imprinted Nanoparticle Receptors in Water

Abstract: Folate receptors are overexpressed on cancer cells and frequently used for targeted delivery. Creation of synthetic receptors to bind folic acid and its analogues in water, however, is challenging because of its complex hydrogen-bonding patterns and competition for hydrogen bonds from the solvent. Micellar imprinting within cross-linkable surfactants circumvented these problems because the nonpolar micellar environment strengthened the hydrogen bonds between the amide group in the surfactant and the template m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…Because the emission of compound 10 and 12 was quite weak in 50 mM Tris buffer (pH 7.3), for the purpose of comparisons, we used ITC binding data exclusively in this study. We have in multiple cases confirmed that binding constants and stoichiometry obtained from these two techniques agree with each other …”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Because the emission of compound 10 and 12 was quite weak in 50 mM Tris buffer (pH 7.3), for the purpose of comparisons, we used ITC binding data exclusively in this study. We have in multiple cases confirmed that binding constants and stoichiometry obtained from these two techniques agree with each other …”
Section: Resultssupporting
confidence: 76%
“…The excellent functional‐group compatibility of the click reaction gives us much flexibility in the design of surface cross‐linkers and different ways of surface‐cross‐linking. Diazide 2 is our most commonly used surface‐cross‐linker (Scheme ) . Since flexibility of the surface‐cross‐linker and surface ligand is important to the binding of MINPs, we designed two diazide cross‐linkers 4 and 5 from ketone 6 that was prepared in one step from commercially available 1,3‐dichloroacetone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, its thiouronium group can bind the negatively charged phosphonate through a hydrogen bond‐reinforced salt bridge, similar to other cationic groups such as guanidinium and amidinium. We recently found this particular salt bridge had sufficient stability for the micellar imprinting as long as the FM possesses significant hydrophobicity for its inclusion in the micelle . Second, the FM contains a methacrylate group and thus can be co‐polymerized with the methacrylate of 1 and DVB to become part of the core of the MINP.…”
Section: Resultsmentioning
confidence: 99%